Three Essays in Textual Disclosure - Soliman, Marwa (Université d'Ottawa / University of Ottawa, 2022)
In recent years, corporate textual disclosure has gained considerable attention in accounting and finance research. The textual disclosures complete the picture of a firm's economic performance in addition to the quantitative information. Many studies have investigated various determinants and consequences of textual disclosure attributes. This thesis aims to contribute to this growing strand of literature that studies the drivers of the textual attributes of narrative disclosure. The thesis consists of three essays related to political uncertainty, CEO characteristics, and corporate social responsibility. The first essay (Chapter 2) investigates the impact of political uncertainty on the informativeness of a firm's narrative disclosure. Using conference calls, the results show that firms exposed to political uncertainty provide less readable disclosure, more ambiguous tone, and rely more on scripted responses to analysts. Further analysis reveals that obfuscatory disclosure has predictive power over a firm's future poor performance, suggesting that managers use obfuscation to opportunistically mask poor future performance during high political uncertainty periods. The second essay (Chapter 3) examines the impact of the CEO's tenure on the firm's disclosure complexity. Based on upper echelon theory, the results show that early tenured CEOs with greater career concerns have more incentive to provide more readable disclosure to affect the market perception about their ability. However, long-tenured managers get more entrenched and provide obfuscated disclosure. In addition, the results indicate that the effectiveness of different governance mechanisms in improving the quality of a firm narrative disclosure depends on the CEO's tenure. In particular, board oversight (internal governance by subordinate executives) is more effective in constraining new (long-tenured) CEOs' myopic disclosure practices. The third essay (Chapter 4) explores the relationship between corporate social responsibility (CSR) orientation and textual attributes of financial disclosures. The results show that firms with high CSR orientation provide more readable disclosures and use a less ambiguous tone in their annual reports. These findings are consistent with the notion that managers in CSR-conscious firms adhere to high ethical standards and commit to improving the transparency of their firms' financial disclosures. In addition, the study provides evidence that corporate governance mechanisms and CSR are substitutes for each other to ensure transparent disclosure. Overall, the findings of these studies provide insights to the investing community, the firm's board of directors, and standards-setters to better understand the implications of firm CSR engagement, political exposure, and CEO characteristics in financial reporting contexts beyond quantitative metrics.
Keywords: Narrative disclosure; Disclosure complexity; Political uncertainty; CEO tenure; Career concern; Corporate social responsibility